Maternal mortality : report of meeting held at Friends' House. Euston Road on November 15, 1932 (London : Maternal Mortality Committee)
1932-11 1932 1930s 36 pages adoped [adopted] in greater or less degree by the Local Authorities throughout England and Wales. Of course, the system is not yet complete or perfect. That is undoubtedly so, but there can be no question that the public facilities provided for women in childbirth are vastly better than they were at no very distant period of time and that the progress — it may be unequal in its pace — is constant. Let me mention one or two particulars to which I have referred which have already been taken up. The General Medical Council have promptly set to work to revise the medical curricula of all the medical schools. There has been improvement in the supervision and the work of the midwives ; 1,200 ante-natal centres have been established throughout the country and 3,180 maternity beds directly or indirectly under the Local Authorities and 3,600 more in the transferred municipal hospitals, giving a total of 6,800 beds available, excluding a large number of maternity beds in the voluntary hospitals. This has been the work of the Ministry and of the Local Authorities supplemented by the voluntary work to which one would desire to pay a special tribute of praise and thanks. Now, Lady Iveagh, you have referred to the circumstance which is, if I may say so, in the forefront of the minds of all of us, that we have not yet seen any definite effect of this work upon the maternal death-rate. That is the leading fact, the fact which leads us in our efforts for advance. That decrease of the maternal death-rate which is set before us as our goal we do not yet see, and that is a disappointment. It is a disappointment that we have not yet begun to reap in visible figures any substantial results from the measures already taken, and, therefore, we record this afternoon that we are not content. We are not content and we will not accept the facts as they are until we do begin to reap that substantial result in an actually falling death-rate which we desire to see from the efforts of the sort which I have described. Now the Maternal Mortality Committee, for our guidance, to help us, in the spirit of common sense, which, if I may say so, is indicated in the whole of its Report, has emphasised the fact that we must realise that time is a factor. Time is a factor in the work which we have before us. They have told us that it is a long journey which we have to tread. Where education is involved as one of the essential factors for the improvement which we desire to see, we must realise that the journey takes time to complete. The effects of the better training of the doctors and midwives of the future have to be allowed time to tell. And I must add this, and this is one thing which I have particularly in my mind to say to you who will so fully realise its practical bearing, I must add that the younger women of England have also to be trained and educated by the efforts of propaganda, the efforts of education for which you are so (7) 292/824/1/45